Therapeutic potential of polyphenols against aging- induced idiopathic pulmonary fibrosis (IPF) via Bioinformatics analysis - Ankit Tripathi; Deepika Tripathi; Manish Shukla; Meenakshi Sharma (Elsevier, 2024)
Background: Hyperactivation of Akt/mTORC1 is known to be the mechanistic driver for idiopathic pulmonary fibrosis (IPF) induction in elderly population. Stimulation of Aryl hydrocarbon receptor (AhR) under physiological stress is largely associated with Akt/mTORC1 inhibition upon aging. This in turn restores the normal autophagy and thereby curbs IPF induction in aged population. Method: To repurpose and validate polyphenol formulation against aging- driven lung fibrosis, molecular docking of the compounds selected from literature was performed. Findings from molecular docking were then being cross-confirmed by ADMET analysis unveiling the pharmacological aptness of docked molecules with the shortlisted receptors. Results: The present study aimed at investigating the possible dietary flavonoid therapy (Quercetin, baicalin, luteolin, curcumin, rutin, and epigallocatechin gallate (EGCG)) attenuating the activation of mTORC1 in the lung epithelia by molecular docking approaches to ascertain the binding affinities of phytoflavonoids towards AhR and FK506 binding protein (FKBP12) over the known IPF synthetic inhibitors - pirfenidone and nintedanib. Additionally, the toxicity profile of ligands was confirmed by ADMET. Baicalin and luteolin demonstrated the best free energy analysis over other phytochemicals and commercial IPF inhibitors (pirfenidone and nintedanib) used in the study. Additionally, the findings from docking study were further confirmed by ADMET analysis indicating the therapeutic potential of baicalin and luteolin in augmenting autophagic signaling and thus may confer significant resistance against lung scarring in aged population. Conclusion: Flavonoids formulations having mTORC1 suppression by AhR activation leading to autophagic induction can be considered as a therapeutic moiety for mitigating IPF during biological aging.